PhagesDB: the actinobacteriophage database - Russell, Daniel A. (Bioinformatics, 2017)
The Actinobacteriophage Database (PhagesDB) is a comprehensive, interactive, database-backed website that collects and shares information related to the discovery, characterization and genomics of viruses that infect Actinobacterial hosts. To date, more than 8000 bacteriophages—including over 1600 with sequenced genomes—have been entered into the database. PhagesDB plays a crucial role in organizing the discoveries of phage biologists around the world—including students in the SEA-PHAGES program—and has been cited in over 50 peer-reviewed articles. Availability and Implementation: http://phagesdb.org/ Contact: gfh@pitt.edu